2018
DOI: 10.22230/cjc.2019v44n3a3377
|View full text |Cite
|
Sign up to set email alerts
|

Too Crowded for Crowdsourced Journalism: Reddit, Portability, and Citizen Participation in the Syrian Crisis

Abstract: Background This article explores the complexity of citizen participation in social media and crowdsourced journalism by utilizing the case of r/SyrianCivilWar, the sub-community of Reddit where users discuss the Syrian crisis.Analysis  In examining the limitations and affordances of the platform, the article identifies features that characterize the r/SyrianCivilWar community, namely: algorithmic driven public discourse, deliberative communication, reflexivity and transparency, and database journalism. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In other words, social media has served as a reductionist and essentialist echo chamber for those marginalizing stereotypes pervasive in legacy media. As Merlyna Lim (2013) writes, social media has dramatically accelerated the production and circulation of information, necessitating simpler and shorter narratives, only reinforcing the trend that was already in place in legacy media as it tried to adapt to the increasingly competitive and technologically expedited media environments (see also Lim, 2018;Mitchell & Lim, 2018). Moreover,…”
Section: Discussionmentioning
confidence: 99%
“…In other words, social media has served as a reductionist and essentialist echo chamber for those marginalizing stereotypes pervasive in legacy media. As Merlyna Lim (2013) writes, social media has dramatically accelerated the production and circulation of information, necessitating simpler and shorter narratives, only reinforcing the trend that was already in place in legacy media as it tried to adapt to the increasingly competitive and technologically expedited media environments (see also Lim, 2018;Mitchell & Lim, 2018). Moreover,…”
Section: Discussionmentioning
confidence: 99%
“…Although #sealfie itself generated opportunity, in that it has provided a platform that allows defenders of sealing to come together, it is difficult to assess whether it has had much impact beyond that. Clearly, no deliberative dialogue (see Mitchell & Lim, 2018) took place where opposing views could be discussed, mutually understood, or reconciled. Indirectly, however, it is possible that legacy media's coverage of #sealfie has helped to raise awareness of the issues surrounding sealing in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Though there is much academic research incorporating Reddit threads and user activity (Buozis, 2017; Massanari, 2017; Mitchell and Lim, 2018; Park et al, 2018; Sharma et al, 2017), much of the literature on Reddit is fragmented between the disciplines of communication, sociology, and support-based bodies of literature from varying social science fields. Communication scholars across disciplines have commented on the values of anonymity in high-risk posting (Donath, 1999; van der Nagel, 2013; van der Nagel and Frith, 2015).…”
Section: Describing Reddit: a Coded Languagementioning
confidence: 99%
“…In 2013, Duggan and Smith found that 6% of online users are also Reddit users, with lower age users (18–29) prevailing, and science and technology as the most Reddit-ed topics (Wasike, 2011). Reddit provides a platform that transcends physical, spatial, and temporal boundaries and has been explored regarding crises such as the Boston Marathon bombing, crisis in Syria, and exchange of criminal evidence (Buozis, 2017; Mitchell and Lim, 2018; Suran and Kilgo, 2017). Aside from a forum for public discussion of news, Reddit studies have also involved stigmatic medical topics including addiction, mental health, patient-to-patient support, and regretful decision-making (Bers, 2009; Moore and Abetz, 2018; Sharma et al, 2017; Sowles et al, 2017; Qiu et al, 2011).…”
Section: Anonymous Affordances and Reddit’s Supportive Structurementioning
confidence: 99%